The Relationship between Marketing Creativity and Product Quality to Customer Satisfaction and Loyalty of Coffee MSMEs in Banyuwangi - Lifchatullaillah, Endang; Kowey, Wylda Olivia; Silamat, Eddy (West Science Interdisciplinary Studies, 2025)
This study examines the relationship between marketing creativity, product quality, customer satisfaction, and loyalty in coffee micro, small, and medium enterprises (MSMEs) in Banyuwangi. Using a quantitative approach with 145 samples and data analysis through Structural Equation Modeling (SEM) and Partial Least Squares (PLS), the study investigates how marketing creativity and product quality influence customer satisfaction and loyalty. The results show that both marketing creativity and product quality significantly affect customer satisfaction, with product quality having a stronger impact on customer loyalty. The findings highlight the critical role of creative marketing strategies and high-quality products in fostering customer loyalty and satisfaction, suggesting that coffee MSMEs in Banyuwangi should prioritize these factors to sustain competitive advantage.